2019
DOI: 10.1111/jocn.14806
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ professional values: Influences of experience and ethics education

Abstract: Aims and objectives To measure the professional values of registered nurses and determine whether these values are significantly related to postlicensure ethics education and years of experience. Background Nursing guilds in many countries reference the American Nurses Association's code of ethics to define expected professional nursing values. Strong professional values contribute to high‐quality patient care and are influenced by complex practice environments. Design Causal‐comparative design. Methods A conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 25 publications
(62 reference statements)
3
38
1
2
Order By: Relevance
“…As in other research (Clark ), the students granted more importance to the professional values compared to the nurses. These findings of decreasing professional values do not coincide with other studies (Bijani et al ; Gallegos & Sortedahl ; Monroe, ; Poorchangizi et al ) where the opposite effect was observed. However, our findings about the different appraisal of professional values among students and nurses were recently confirmed in a similar study conducted in Iran, which included the vision of instructor nurses, finding significant differences among the three groups in all the domains analysed.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…As in other research (Clark ), the students granted more importance to the professional values compared to the nurses. These findings of decreasing professional values do not coincide with other studies (Bijani et al ; Gallegos & Sortedahl ; Monroe, ; Poorchangizi et al ) where the opposite effect was observed. However, our findings about the different appraisal of professional values among students and nurses were recently confirmed in a similar study conducted in Iran, which included the vision of instructor nurses, finding significant differences among the three groups in all the domains analysed.…”
Section: Discussioncontrasting
confidence: 95%
“…It is especially important to review the commitment of these expert professionals towards their ethical values. As demonstrated elsewhere, if these nurses incorporate these values in their care, they may become role models in the workplace for nurses in training or with less experience (Monroe, ).…”
Section: Discussionmentioning
confidence: 98%
“…Nursing, as a profession, is beyond a set of skills and techniques; it should be noted that comprehensive care not only covers physical needs but also addresses the values and beliefs of the patients (Berman et al, ). Although there are nurses who are still far from the ethical reality of their job (Campana & Hammoud, ; Monroe, ; Unruh et al, ), some nursing researchers view the performance of this profession based on ethics and believe that nursing professional performance is so mixed with ethics that nursing can be considered as a moral philosophy (Harrison et al, ). Nurses face different ethical issues during their daily clinical activities for different reasons (Zahedi et al, ), such as nursing shortage, emergence of new diseases and use of modern technologies in the hospitals, and complex issues such as declaration of brain death, transplantation, genetic manipulations and artificial insemination.…”
Section: Introductionmentioning
confidence: 99%
“…(20,21) O exercício da advocacia do paciente expressa a ética neste cenário, e se configura como um objetivo do trabalho do enfermeiro frente ao cuidado. (22) A advocacia se constitui por um conjunto de práticas que envolvem esforços do profissional para garantir os interesses dos pacientes, no âmbito dos seus direitos, no acesso à informação para tomada de decisões sobre sua saúde, no alcance de bens e serviços necessários ao seu cuidado. (15,21,23) A defesa do paciente com dor, ou em cuidados paliativos, como apontado nos resultados deste estudo, foi relacionada como campo de práticas de advocacia pelo enfermeiro também em outro estudo.…”
Section: Discussionunclassified